P67 Adolescence, pregnancy, and OUD: creating a clinical decision tree that guides providers through mat for a high-risk obstetrical population. (18th November 2019) - Thompson, M; Jones, C
Abstract : Opioid use in pregnancy is on the rise in the United States. There is limited data regarding management for pregnant adolescents with opioid use disorder (OUD). However, there are best practice recommendations for management of OUD in pregnancy that has been demonstrated to improve maternal, fetal, and neonatal outcomes. Aim: The aim of this presentation is to highlight the demographics of pregnant adolescents with OUD, discuss risk and protective factors, and introduce a clinical decision tree for management of OUD in the inpatient obstetrical setting. According to SAMHSA guidelines, adolescents who are pregnant are more likely than their adult counterparts to have past month opioid use. Many inpatient obstetrical providers do not feel comfortable managing pregnant adolescents with OUD and need additional guidance to provide care according to best practice recommendations. Methods: A literature review has been completed regarding adolescents, pregnancy, and OUD. A clinical decision tree was created by a DNP student and a MFM mentor for an inpatient setting and listeners will be guided through continuation or management of MAT for pregnant adolescents with OUD. Results: The clinical decision tree will be reviewed during the presentation. Conclusion: Knowledge regarding adolescents, OUD, and pregnancy can help adolescent health and obstetrical providers improve maternal, fetal, and neonatal outcomes that are linked to lifelong improvementin health outcomees for both mothers and infants.